Risk factors and prognosis of postoperative delirium in nonagenarians with hip fracture - Zhao, Shengjie; Sun, Tiansheng; Zhang, Jianzheng; Chen, Xiaobin; Wang, Xiaowei (Scientific reports, 2023)
Hip fractures in nonagenarians is one of the great challenges for patients of this age, the family and the larger society. The purpose of this study was to investigate the risk factors and prognosis of postoperative delirium in nonagenarians with hip fracture. 199 Eligible patients were enrolled. Confusion Assessment Method (CAM) were used to identify the delirium. Logistic regressions were used to investigate the effect of 18 pre-existing conditions on postoperative delirium. Prognosis of postoperative delirium in nonagenarians with hip fracture were also be evaluated. The results indicated the following: (1) the prevalence of postoperative delirium among nonagenarians with hip fracture was 28.1% (56 of 199); (2) coexisting disease ≥ 4 (OR = 5.355, 95% CI = 1.394–9.074, P = 0.007), longer admission to operating time (OR = 1.514, 95% CI = 1.247–1.837, P = 0.000), and general anesthesia (OR = 2.086, 95% CI = 1.804–7.968, P = 0.032) were independent risk factors for postoperative delirium in nonagenarians with hip fracture; (3) nonagenarians with postoperative delirium had a predominantly high burden of perioperative complications, long length of stay, and postoperative mortality at 30 days follow-up and 1 year follow-up than the patients without postoperative delirium. The results could enable clinicians to improve outcome after operation in nonagenarians with hip fracture.